Ethical Considerations in Using Social Media to Engage Research Participants: Perspectives of Australian Researchers and Ethics Committee Members. (February 2020) - Hokke, Stacey; Hackworth, Naomi J.; Bennetts, Shannon K.; Nicholson, Jan M.; Keyzer, Patrick; Lucke, Jayne; Zion, Lawrie; Crawford, Sharinne B.
Researchers increasingly use social media (SM) to recruit, retain, and trace participants, yet empirical literature investigating the ethics of engaging participants via SM is lacking. We conducted a survey of 401 Australian researchers and human research ethics committee (HREC) members to examine their experience, attitudes, and ethical concerns toward engaging participants via SM. Data revealed that researchers and HREC members share similar concerns and attitudes about using SM in general and in research. We identified a strong demand for additional support, training, and guidance on SM research ethics. This need reflects researchers' and HREC members' limited confidence and knowledge of ethical issues in this context and a lack of awareness of available SM-specific ethical guidelines.